Dermatitis neglecta -- A dirty dermatosis: Report of three cases - Abhijit Saha; Joly Seth; Amita Sharma; Desharghya Biswas (Wolters Kluwer Medknow Publications, 2015)
Dermatitis neglecta is a condition that results from inadequate frictional cleansing leading to accumulation of corneocytes, sebum and sweat ultimately resulting in hyper-pigmented patch or verrucous plaque. Recognizing this condition avoids unnecessary, aggressive diagnostic and therapeutic procedures. Here we report three cases of dermatitis neglecta in whom the dermatitis developed as a result of intentional neglect of personal hygiene.